Optimized reservoir operation model of regional wind and hydro power integration. Case study: Zambezi Basin and South Africa - Yohannes Gebretsadik; Chas Fant; Kenneth Strzepek (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
The present study develops a reliability assessment method of wind resource using optimum reservoir target power operations that maximizes the firm generation of integrated wind and hydro power. A combined water resources model for a system of reservoirs that implements a priority based linear programing algorithm and a single node power grid system model is implemented on an hourly time step. This model was then accompanied by a genetic algorithm solver to determine optimum operation targets for each storage reservoir aiming at maximizing the 90th percentile power generation produced by the integration of wind and hydro over the entire simulation period. This model is applied on the reservoir storages and hydro power system in the Zambezi River basin to demonstrate how storage reservoirs could be used to offset wind power intermittence in South Africa subjected to different physical and policy constraints. Based on the optimized target operation and hourly data for the year 2010, the water resources system and power interconnection system were simulated together to assess the maximum firm generation of power as a result of the new wind and hydro combination target for storage hydro power plants. The result obtained indicates that high regulation of wind and hydro can be achieved as a result of combined operation and showed an increased level of wind penetration in South Africa's power system over the reference scenario. The results also indicated a reduced level of coal power utilization and less cycling requirement. This will have a positive outcome in terms of contributing to South Africa's goal towards reducing greenhouse gas emissions and the efforts to build green energy supply and resilience to the impacts of climate change.
Keywords: C63; Q25; Q54; 330; wind; hydro power; optimized operation; Zambezi; Congo